Langerin+ CD8α+ Dendritic Cells Drive Early CD8+ T Cell Activation and IL-12 Production During Systemic Bacterial Infection - Prendergast, Kelly A.; Daniels, Naomi J.; Petersen, Troels R.; Hermans, Ian F.; Kirman, Joanna R. (Frontiers in Immunology, 2018)
Bloodstream infections induce considerable morbidity, high mortality and represent a significant burden of cost in health care; however, our understanding of the immune response to bacteraemia is incomplete. Langerin+ CD8alpha+ dendritic cells (DCs), residing in the marginal zone of the murine spleen, have the capacity to cross-prime CD8+ T cells and produce IL-12, both of which are important components of antimicrobial immunity. Accordingly, we hypothesised that this DC subset may be a key promoter of adaptive immune responses to blood-borne bacterial infections. Utilising mice that express the diphtheria toxin receptor under control of the langerin promoter, we investigated the impact of depleting langerin+ CD8alpha+ DCs in a murine model of intravenous infection with Mycobacterium bovis bacille Calmette Guerin (BCG). In the absence of langerin+ CD8alpha+ DCs, the immune response to blood-borne BCG infection was diminished: bacterial numbers in the spleen increased, serum IL-12p40 decreased, and delayed CD8+ T cell activation, proliferation and IFN-γ production was evident. Our data revealed that langerin+ CD8alpha+ DCs play a pivotal role in initiating CD8+ T cell responses and IL-12 production in response to bacteraemia, and may influence the early control of systemic bacterial infections.